Pemberdayaan masyarakat di Desa Balai Makam dalam pemanfaatan bonggol pisang sebagai rintisan Usaha Mikro Kecil Menengah (UMKM) - Tetty Marta Linda; Sezhianindi Firiola; Rahmah Agnissah; Binar Robinson M; Muhammad Rinaldi; Sri Ramadhani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Banana hump is one part of the banana plant that is still very rarely used. The Banana hump can be an item with a selling value because it contains high carbohydrates, fiber, and calcium to be an alternative food ingredient. The banana hump can be turned into nutrient-rich flour. Community empowerment to process banana hump into something useful and can be a pilot business for residents is one of the keys to this success of this activity. This service will provide benefits to various parties, including for community service participants, for the counseling implementation team, for universities, and for the government. The purpose of this activity is to introduce and train the skills of making flour made from banana humps, which we named